Kesalahan siswa kelas VII SMP Negeri 19 Mataram Tahun Ajaran 2020/2021 dalam menyelesaikan soal cerita pada materi himpunan ditinjau dari prestasi belajar - Guntoro Edy Prayogi; Sripatmi Sripatmi; Muhammad Turmuzi; Hapipi Hapipi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to describe the mistakes made by the VIIA grade students of SMP Negeri 19 Mataram in solving story questions about the set material in terms of learning achievement. With the research subject, namely 6 students of class VIIA which has been selected based on learning achievement. This research is a descriptive qualitative type with research instruments in the form of written test sheets and interview guidelines. The data analysis technique was carried out by the students completed the questions using the Polya analysis or not, if using the Polya analysis, the stages were correct or not, if using the Polya analysis with the correct steps, the students' answers would be analyzed using the Polya analysis. The results of the study were at the stage of understanding the problem, the subject made mistakes 16.66% with a small category, at the stage of choosing the right problem-solving strategy made an error 20% with a small category, at the stage of solving the problem subject made a mistake 51.66% with the high category and at the stage of re-checking subjects made mistakes 64,58% with the very high category.